Mewujudkan perbankan syariah berkelanjutan: Strategi perbankan syariah dalam meningkatkan pertumbuhan dana pihak ketiga - Kamarullah, Khalifaturrahman (Maliki Interdisciplinary Journal, 2024)
Islamic banking is a banking system based on sharia principles that operates without the element of usury. Third party funds are an important indicator to measure the performance of a bank. The growth of deposits is crucial for the continuity of Islamic banking. Some of the challenges faced include competition with conventional banks and the issue of Islamic financial literacy. The main strategies discussed include digitizing services with mobile banking, product innovation that suits the needs, increasing literacy through public education, and applying the principle of sustainability in fund management. The implementation of these strategies is expected to increase the growth of deposits in a sustainable manner so as to support the operations and growth of Islamic banking in Indonesia.